Checkpointing distributed computing systems: an optimisation approach. (18th March 2020) - Mansouri, Houssem; Pathan, Al-Sakib Khan
The intent of this paper is to propose an optimisation approach for a new coordinator blocking type checkpointing algorithm to ensure reliability and fault tolerance in distributed computing systems. More precisely, we have undertaken an exhaustive study of the reference coordinator blocking checkpointing algorithms proposed in the literature. This study enables us to characterise them in order to benefit from their positive aspects and guides us to put forward a new optimisation approach based on dependency matrices offering the advantage of distribution. Therefore, we can optimise the checkpointing execution/blocking time to the strict necessity compared to the message computation overhead. The simulation studies prove the effectiveness of our optimisation compared to other referenced algorithms.